To solve this system of equations by elimination, we first want to eliminate one of the variables by adding the two equations together. In this case, we can multiply the first equation by 2 to make the coefficient of x in both equations equal and have opposite signs:
-8x - 16y = -40
8x + 3y = 1
Now we can add the two equations together:
-8x - 16y + 8x + 3y = -40 + 1
-13y = -39
Divide both sides by -13 to solve for y:
y = 3
Now that we have found the value of y, we can substitute it back into one of the original equations to solve for x. Let's use the first equation:
-4x - 8(3) = -20
-4x - 24 = -20
-4x = 4
x = -1
Therefore, the solution to the system of equations is x = -1 and y = 3.
solve the system of equations by elimination. -4x - 8y = -20 and 8x + 3y = 1
1 answer